PHYSICAL EDUCATION IN EARLY CHILDHOOD EDUCATION (Fiep Bulletin - online, 2013)
This work is a report of survey conducted during the course of Stage Supervised: Search of Educational Practice Course for Graduate Education in Physics. While intrigued scholars in the thought of teaching practice of physical educator with the children of Child Rearing, a fact that during the speeches of probation, led us to inquire about the importance of this discipline, through its object the study of human movement, in the process Development of the subject in Child Rearing. With this research-action aimed to analyze how the teachers of Education Child understood the lessons of Physical Education, if they believed these important lessons, and if the teachers watched influences school of Physical Education in the process of development and learning of children. To meet these goals we conducted interviews with all teachers of the Child Education Center (IEC) which developed the stage. The interviews were analyzed based on analysis of content and in the field of daily speeches made during the internship. We noticed the Fitness is understood by teachers as an important practice in Child Rearing. However that amount is not related to the specific work of the physical educator, but the specific knowledge of the business, identified as the most likely to work with the movement of children. We therefore consider it essential that the work of physical educator in Children's Education is held in partnership with other teachers, view the child as a whole. Also shows the need for professional inclusion of Physical Education in CIS's.
Keywords: Physical Education; Child Education -; Teaching